Postscript: Comparative Research and the 'New World Order' - Bergquist, Charles (Labour / Le Travail, 1996)
Discusses the papers on the labour history of Australia and Canada presented in the volume. Argues that more attention should have been paid to the factors that enabled union incorporation in Australia half a century in advance of Canada as well as to the labour aspects of both countries' export economies. Compares the Argentinean experience (the author is a Latin America specialist) with that of Canada and Australia. Concludes that, in the era of the neoliberal new world order, comparative studies like these are valuable since the labour movement is vital to the health of democracy.
Keywords: AUSTRALIA; Canada; Comparative studies; ECONOMIC structure; INCORPORATION; Labor; Labor Unions; Labor movement; RELATIONS of production